Reading the Dynamics of Democracy in Organizing General Elections in Indonesia - Arifin, Ridwan (Law Research Review Quarterly, 2018)
The holding of elections in Indonesia is of public concern, not only on a national scale but also internationally. As a country with a majority Muslim population with various ethnicities, religions, and beliefs, but is considered capable of carrying out democracy properly, one of them through elections, Indonesia has become the public spotlight. Various successes and critical notes on the holding of elections in Indonesia colors the dynamics of the general election journey itself.